THE ROLE OF THE ISLAMIC EDUCATION SUBJECT AND LOCAL TRADITION IN STRENGTHENING NATIONALISM OF THE BORDER SOCIETY (STUDY IN TEMAJUK VILLAGE SAMBAS REGENCY OF WEST BORNEO) - Muzayanah, Umi (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Temajuk village is one of the areas in the regency of Sambas, West Borneo, which is a bordering area with Malaysia. The location which is far from the center of government and close to the territory of another country can, to some extent, threaten the border society’s nationalism. Through a qualitative approach, this study examined the role of the Islamic education subject (PAI) and the local tradition (Saprahan) in strengthening the nationalism of the border people. The results showed that at least there are three teaching materials of Islamic Education (PAI) relevant to the values of nationalism i.e., democracy, tolerance, and unity and harmony. Such materials have a strategic role in providing nationalism reinforcement for students at a senior high school level. Meanwhile, the Saprahan tradition which has been held fast by Temajuk people showed that their nationalism principles are contained therein, i.e., unity, equality, and performance. The tradition also has a social function for the inhabitants of Temajuk to meet their basic and secondary needs.